2016
DOI: 10.1002/art.39462
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Analgesics and the Risk of Serious Infections Among Patients With Rheumatoid Arthritis: A Self‐Controlled Case Series Study

Abstract: Objective Animal and in vitro studies suggest that certain opioid analgesics impair crucial immune functions. We sought to determine if opioid use is associated with an increased risk of serious infections in patients with rheumatoid arthritis (RA). Methods We conducted a self-controlled case series analysis on a retrospective cohort of 13,796 patients with RA enrolled in Tennessee Medicaid (1995–2009). We performed within-person comparisons of the risk of hospitalizations for serious infections during perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 52 publications
7
65
2
2
Order By: Relevance
“…A case-control study conducted among older adults enrolled in a private health insurance system reported a 39% increased odds of current opioid exposure among pneumonia cases compared with controls [18]. Similarly, in a study conducted among patients with rheumatoid arthritis enrolled in a State Medicaid program, periods of current opioid use were associated with a 38% increased risk of serious infections (including pneumonia, bacteremia, meningitis/encephalitis, septic arthritis/osteomyelitis, endocarditis, pyelonephritis and cellulitis) compared with periods of non-opioid use [19]. More recently, a nested case-control study, conducted in a population of subjects aged 5 years or older enrolled in a State Medicaid program, reported a 62% higher risk of laboratory-confirmed invasive pneumococcal disease among current users of opioids compared with past users [20].…”
Section: Supporting Evidence From Recent Studies Among Humansmentioning
confidence: 94%
See 3 more Smart Citations
“…A case-control study conducted among older adults enrolled in a private health insurance system reported a 39% increased odds of current opioid exposure among pneumonia cases compared with controls [18]. Similarly, in a study conducted among patients with rheumatoid arthritis enrolled in a State Medicaid program, periods of current opioid use were associated with a 38% increased risk of serious infections (including pneumonia, bacteremia, meningitis/encephalitis, septic arthritis/osteomyelitis, endocarditis, pyelonephritis and cellulitis) compared with periods of non-opioid use [19]. More recently, a nested case-control study, conducted in a population of subjects aged 5 years or older enrolled in a State Medicaid program, reported a 62% higher risk of laboratory-confirmed invasive pneumococcal disease among current users of opioids compared with past users [20].…”
Section: Supporting Evidence From Recent Studies Among Humansmentioning
confidence: 94%
“…Importantly, each of these studies consistently reported that patients using long-acting and high potency opioid formulations, opioids at high doses and opioids previously described as exhibiting immunosuppressive properties (i.e., morphine, codeine, fentanyl and methadone) had the highest risk for infection. The studies also noted a high risk for infections among patients recently initiating opioid use [18][19][20].…”
Section: Supporting Evidence From Recent Studies Among Humansmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous research has associated opioid use with a higher risk of pneumonia in different population groups [13][14][15][16][17]. However, the risk of pneumonia among opioid users with cognitive disorders has not been studied previously.…”
Section: Introductionmentioning
confidence: 99%